Ausrnelt Technology, Flexible, Low Cost Technology For Copper Production In The 21st Century (Invited) - Joseph Sofra (The Minerals, Metals and Materials Society, 2003)
It has become increasingly evident that sustainable metals production in the 21" century requires producers to balance the needs of cost effective, high value production with that of responsible plant operation. This is becoming more difficult as lower grade and more complex feed materials, including recycled scrap and residues, arc being processed to reduce production costs and decrease exposure to primary metal market fluctuations. One particular facet of the metals industry facing these challenges in the 21 st century arc copper producers. The recent steady decline in the copper price has seen the industry cut expenditure, tighten control on income streams and focus on high returns on capital investment. For these reasons copper producers arc looking towards flexible technologies that can deliver high value products, with minimal environmental impact at low capital and low sustainable operating costs. Ausmelt's Top Submerged Lancing (TSL) technology for copper production is a low cost, proven technology for the processing of both primary and secondary copper materials. Both the smelting and converting operations introduce significant advantages in environmental performance, improved process efficiencies and high rates of metal recovery. Ausmelt has made significant gains in the past 4 years in establishing a strong market position for its copper technology. New installations in China, South Africa and India as well as existing operations in Zimbabwe and China have demonstrated its effectiveness. This paper reviews the application of Ausmelt Technology for both smelting and converting of primary and secondary sources. It discusses Ausmelt's design and implementation philosophy, and how this philosophy meshes with the needs of the end user.